Shedding light into rural electrification and health: evidence from Brazil - Brancher, Marco Capraro (2019)
This paper investigates the impacts of electricity on health outcomes in Brazilian rural areas. An instrumental variable difference-in-differences approach was addopted, exploring a federal electrification program as source of exogenous variation in the probability of beign connected to the grid. Additionally, the municipality land gradient was also explored as source of exogenous variation, since the electrification program eligibility rule was not sharp. The main findings are in line with the international literature. Electrification reduces the incidence and mortality rate of some respiratory diseases with relevant gender-heterogeneity. Moreover, it has negative impacts on cancer mortality rate. A result that was not expected is that the electrification did not had any effect on intestinal infections.